Determinants of Weight Changes During the First 96 Hours of Life in Full-Term Newborns - Fonseca, MJ (2014)
Background: Newborn weight loss (NWL) in the first 3 days of life is around 6 percent of birthweight (BW). We aim to describe the determinants of an excessive and insufficient NWL in the first 96 hours of life. Methods: A sample of 1,288 full‐term singletons without congenital abnormality belonging to Generation XXI birth cohort was selected. Newborns were recruited in 2005–2006 at all public units providing obstetrical and neonatal care in Porto, Portugal. Information was collected by face‐to‐face interview and additionally abstracted from clinical records. Anthropometrics were obtained by trained examiners and newborn weight change (NWC) was estimated as (weight–BW)/BW × 100. We categorized NWL as excessive (below 10th percentile of the sample distribution of NWC: ≤−9.4% of BW), normal (between 10th and 90th percentiles: −9.3 to −4.2%) and insufficient (above 90th percentile: ≥ −4.1%). Adjusted odds ratios (OR) and 95 percent confidence intervals (CI) were calculated using multinomial regression models. Results: Excessive NWL was positively associated with maternal age ≥40 years (OR = 3.32, 95%CI 1.19–9.25), maternal education (OR = 1.04, 95% CI 1.00–1.09), cesarean delivery (OR = 2.42, 95% CI 1.12–5.23), and phototherapy‐treated jaundice (OR = 1.69, 95% CI 1.00–2.87). Insufficient NWL was positively associated with low BW (OR = 2.68, 95% CI 1.13–6.33), and formula/mixed feeding (OR = 1.74, 95% CI 1.13–2.66). Conclusion: Excessive NWL was positively associated with maternal age and education, cesarean delivery, and phototherapy‐treated jaundice. Insufficient NWL reflected child's feeding. As breastfed newborns did not lose weight excessively, but newborns with formula/mixed feeding had insufficient NWL, our study supports that breastfeeding provides excellent nutrition during this period.